2004
DOI: 10.1111/j.1460-9568.2004.03712.x
|View full text |Cite
|
Sign up to set email alerts
|

A single high dose of cocaine induces behavioural sensitization and modifies mRNA encoding GluR1 and GAP‐43 in rats

Abstract: Neuroadaptive changes underlying repeated exposure to cocaine-induced behavioural sensitization have been related to modification in the pattern of synaptic connectivity and excitatory transmission. Remarkably, even a single exposure to abused drugs is sufficient to elicit lasting behavioural sensitization. The present study investigated whether in Sprague-Dawley rats a single, behavioural sensitizing dose of cocaine is sufficient to induce changes in the mRNA levels of growth-associated protein 43 (GAP-43), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
(39 reference statements)
2
33
1
Order By: Relevance
“…Sensitization has been suggested to be important during the transition from recreational to compulsive cocaine use, and this idea has been argued most formally by proponents of the incentive-sensitization theory of addiction Berridge, 1993, 2001). In animals, sensitization to the locomotor-stimulating effects of drugs such as cocaine has been demonstrated for years and a great deal is known about its neurobiological mechanisms (Post, 1980;Zahniser et al, 1988;Kalivas and Duffy, 1993;Churchill et al, 1999;Grignaschi et al, 2004). However, it is not clear whether sensitization is seen in humans and nonhuman primates (Bradberry, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization has been suggested to be important during the transition from recreational to compulsive cocaine use, and this idea has been argued most formally by proponents of the incentive-sensitization theory of addiction Berridge, 1993, 2001). In animals, sensitization to the locomotor-stimulating effects of drugs such as cocaine has been demonstrated for years and a great deal is known about its neurobiological mechanisms (Post, 1980;Zahniser et al, 1988;Kalivas and Duffy, 1993;Churchill et al, 1999;Grignaschi et al, 2004). However, it is not clear whether sensitization is seen in humans and nonhuman primates (Bradberry, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitizing drug regimens may also increase drug reward/ incentive, as they can enhance later acquisition of drug selfadministration (reviewed in Berridge 1993, 2001). Several groups have demonstrated that behavioral sensitization can be induced by a single injection of cocaine or amphetamine (Robinson et al 1982;Post et al 1987;Vanderschuren et al 1999;Grignaschi et al 2004). Studies examining stimulant-induced sensitization across adolescence have produced mixed results.…”
Section: Introductionmentioning
confidence: 97%
“…Morphine sensitization is associated with decreased GluR2 expression in both the amygdala and the dorsal hippocampus with no changes in GluR1 levels in the hippocampus (Grignaschi et al, 2004;Sepehrizadeh et al, 2008). This could lead to enhanced levels of calcium-permeable AMPA receptors thought to underlie synaptic plasticity.…”
Section: Neurochemistry/neuropharmacologymentioning
confidence: 99%